A universal fracture analysis framework for staggered composites composed of tablets with different wavy topologies. (June 2021) - Liu, Junjie; Wei, Xiaoding
Highlights: A rigorous fracture analysis is performed on staggered composites composed of different wavy tablets using the "fishnet" homogenization algorithm. Effects of tablet waveforms on the tearing modulus of staggered composites have been systematically investigated. Our model theoretically proves that using triangular or trapezoidal tablets has advantages in optimizing the material properties over other tablet topologies. Abstract: In this study, we investigate in-depth the critical role of the tablet waveform in the fracture mechanics of staggered composites using the "fishnet" homogenization algorithm. A multi-scale fracture analysis protocol has been established for the Mode I crack in staggered composites containing various types of wavy tablets – from anti-trapezoidal to triangular ones. Our analysis finds that the staggered microstructure provides the Mode I crack in the composites a displacement field identical to that of the Mode III crack in an ideal elasto-plastic media. Through parametric studies, our model elucidates the advantages of triangular or trapezoidal tablets over other tablet waveforms in the optimization of the tensile strength and fracture properties of staggered composites.